Counselling Methods for Drug Users and Father Absence as Triggering Factors for Drug Abuse - Abhista Andikaputra, Andea Muhammad; Jaro'ah, Siti (Proceedings of The International Conference on Psychology and Education, 2026)
The issue of drug abuse in Indonesia continues to be an important concern, with data from the Ministry of Health in 2025 and the National Narcotics Agency (BNN) showing that 2.2 million adolescents in Indonesia are drug users. Related to this, the efforts made by BNN are to provide rehabilitation facilities in the form of counselling. In this research, the author will use the literature review method to observe and compare it with the observation and interview data that the author gets in the field. Through this research, the author found that the most appropriate method to handle individuals, especially in cases of drug abuse, is Cognitive Behavioural Therapy. Then the author also found that the main cause of drug abuse among children is the lack of a father's role, both physically and psychologically, a condition known as “fatherless”.